English Morphological Awareness and Cultural Mindset in Indonesian College Students’ Descriptive Text Writing: Challenges, Strategies, and Digital Technology Utilization - Suadi Suadi; Fitriani; Sulaiman (SALEE: Study of Applied Linguistics and English Education, 2026)
English morphological awareness, cultural mindset, writing experience, and digital technology utilization significantly influence writing development, yet their interaction effects remain underexplored. Integrated investigation of morphological, cultural, experiential, and technological influences on writing development remains warranted. This study employed qualitative descriptive study. A total of 92 non-EFL Indonesian undergraduate students voluntarily participated in this study. The findings revealed morphological errors in students’ descriptive texts, comprising derivational and inflectional errors. Inflectional errors predominantly involved incorrect present-tense forms, followed by incorrect noun formation, comparative forms, third-person singular verb forms, and adverb formation. Moreover, students demonstrated that cultural mindset can influence vocabulary choice, word formation, expressions, focus of description, and the details students include in their descriptive texts. With regard to writing experience, most participants perceived English writing as challenging due to limited writing practice, inadequate vocabulary mastery, grammatical inaccuracy, and low self-confidence. To address these difficulties, participants identified several effective strategies, including peer feedback, regular writing practice, gradual writing development from simple structures, vocabulary enrichment, extensive reading, grammar improvement, and confidence building. The participants also reported that digital applications, such as Grammarly, grammar checker, DeepL, Google Translate, Duolingo, and ChatGPT, positively supported their writing development. This study concludes that integrated morphological awareness, cultural understanding, learning strategies, and digital technologies strengthen English writing proficiency.